PENERAPAN MEDIA PEMBELAJARAN FLASH CARD DALAM MENINGKATKAN HASIL BEAJAR SISWA MATERI PENGGOLONGAN HEWAN PADA KELAS IV SD NEGERI 200107 PADANGSIDIMPUAN - Andika, Vivi; Batubara, Ulfah Nury; Theresia, Monica (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2024)
This research aims to determine the use of flash card media in class IV students at SD Negeri 200107 Padangsidimpuan on animal classification material. This research medium used PTK research (Classroom Action Research). Data collection techniques used were observation and tests. The subjects in this research were all 19 class IV students at SD Negeri 200107 Padangsidimpuan. Meanwhile, the object of the research is improving student learning outcomes in animal classification material. Based on the results of Cycle I, the final percentage of observation results was found to be 65, this achievement indicates the poor category. The results of observations of student activities also show that students' activities when expressing opinions and giving responses are less active. Meanwhile, in cycle II, the results of observations from learning activities using Flash Card media showed that the score was 81.66, this achievement shows the good category. The results of the first cycle test concluded that it was known that only 9 students had completed it or around 47.37%. The number of incomplete students was 10 students or 52.63% with an average test score of 73.89. This average score shows that students are still below the KKM value applied. Meanwhile, the results of the second cycle test were 16 students who completed the applied KKM score or 84.21%. This is influenced by students' activeness during learning where the average test score obtained was 81.68, which is in the good category.